Levers - Mattern, Joanne, 1963- (Minneapolis, MN : Bellwether Media, Inc., 2020)
Relevant images match informative text in this introduction to levers. Intended for students in kindergarten through third grade.
What are levers? -- How do levers work? -- Levers in our lives.
Includes bibliographical references (page 23) and index.
2.8
K-3
Keywords: Levers -- Juvenile literature; Levers; Readers (Elementary) -- Nonfiction